Problematic Hadiths on Aqīdah in the Book “Tanya Jawab Agama” Volumes 1–3 by the Majelis Tarjih and Tajdid of Muhammadiyah Central Leadership - Matojir, Saprul; Parjiman; Husna, Jannatul (Taqaddumi: Journal of Quran and Hadith Studies, 2025)
Muhammadiyah as a movement for the purification and modernization of Islam, emphasizes the use of mutawātir hadiths in the realm of faith according to the tarjih method. However, many unclear qualities of hadith are still used. This study aims to evaluate the quality of hadith and examine the consistency of the application of the tarjih method in the book. This study was conducted through a qualitative approach, and the type of research is descriptive-analytical with the hadith criticism method, which involves evaluating the consistency of the application of the tarjih principle in each hadith used. The research results indicate that the application of the tarjih methodology in the Tanya Jawab Agama volumes 1-3 regarding hadiths on aqīdah is inconsistent, particularly in classifying the quality of the hadiths. It was found that there are three mutawātir hadiths, seven saḥīḥ aḥād hadith, and three da'īf hadiths. Some hadiths are presented only in translation without any explanation of their quality, while others are assessed inconsistently.